Real Time Measures of Prestin Charge and Fluorescence during Plasma Membrane Trafficking Reveal Sub-Tetrameric Activity - Bian, Shumin (Public Library of Science, 2013)
Prestin (SLC26a5) is the outer hair cell integral membrane motor protein that drives cochlear amplification, and has been described as an obligate tetramer. We studied in real time the delivery of YFP-prestin to the plasma membrane of cells from a tetracycline-inducible cell line. Following the release of temperature block to reinstate trans Golgi network delivery of the integral membrane protein, we measured nonlinear capacitance (NLC) and membrane fluorescence during voltage clamp. Prestin was delivered exponentially to the plasma membrane with a time constant of less than 10 minutes, with both electrical and fluorescence methods showing high temporal correlation. However, based on disparity between estimates of prestin density derived from either fluorescence or NLC, we conclude that sub-tetrameric forms of prestin contribute to our electrical and fluorescence measures. Thus, in agreement with previous observations we find that functional prestin is not an obligate tetramer.